Galatians - Esler, Philip Francis (New Testament readings., 1998)
Paul's letter to the Galatians, sometimes known as the Magna Carta of Christian liberty, is central to the understanding of the relation of Paul and the Law and is packed with crucial historical, social and theological material. Philip F. Esler provides a detailed and accessible interpretation of the text, which draws on contemporary and modern literary models. He outlines the problems often associated with reading Galatians, the context of the text, the rhetoric of the text and the intercultural and social implications of Galatians. Galatians includes comprehensive indices of anci.